Wigner surmise for Hermitian and non-Hermitian chiral random matrices - Akemann, Gernot; Bittner, Elmar; Phillips, M. J.; Shifrin, L. (Physical review. E, Statistical, nonlinear, and soft matter physics, 2009)
We use the idea of a Wigner surmise to compute approximate distributions of the first eigenvalue in chiral random matrix theory, for both real and complex eigenvalues. Testing against known results for zero and maximal non-Hermiticity in the microscopic large-N limit, we find an excellent agreement valid for a small number of exact zero eigenvalues. Compact expressions are derived for real eigenvalues in the orthogonal and symplectic classes and at intermediate non-Hermiticity for the unitary and symplectic classes. Such individual Dirac eigenvalue distributions are a useful tool in lattice gauge theory, and we illustrate this by showing that our results can describe data from two-color quantum chromodynamics simulations with chemical potential in the symplectic class.
Gesehen am 13.11.2017